Kekuatan Hukum Kebijakan Pemerintah Daerah Dalam Menerbitkan Keputusan (Beschikking) Dihubungkan Dengan Penerapan Asas Praesumptio Iustae Causa - Pery Rehendra Sucipta (Jurnal Selat, 2014)
Executant of local governmentin carrying out their duties, authorities, obligations and responsibilities and because of higher legislation authority can establish regional policy which is defined in local regulation, regional regulation and other local conditions. The publishing of regional head decreerelated to arrangement the cost of Land and Building Tax as arulein terms of implementation for using the Land and Building Tax isunder the authority of Subang district Government .Accordingly, this study focused on the problem: (1)How is the power of Subang district decreeNo. 973/Kep.604-Dipenda/2005 about BP-PBB in Subang district associated with the praesumptio iustae causa. This research obtained through normative juridical approach. The nature of study for this research is descriptive analysis. Based on this research we can conclude that: first, Subang District Decree No.973/Kep.604-Dipenda/2005 About BP-PBB in Subang district eligible formal andmaterial requirements for making a decision, so the decision is validaccording to the lawandit can produce the principle of praesumptio iustae causa. Keywords: Policy, Government, Regions, Decision